Implementasi Bank Wakaf Mikro Digital Terhadap Peningkatan Produk Pembiayaan Usaha Mikro Kecil Menengah di Indonesia - Pertiwi, Novi Dian; Azizah, Ismatul; Yusuf, Yusuf (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2022)
Digital micro Bank communal financial institution expected can manage the the asset to be giving the benefit in the form of prosperity to people. This research aim to to analyse management of digital micro communal ownership bank which done by the Moslem law financial institution get trust from Kementerian Agama as organizer of money communal ownership in Indonesia so in this time. This Descriptive qualitative research written pursuant to study literasi Conclusion of research is digital micro communal ownership bank financial institution require to optimal of application implementation BWM digital to deliver prosperity and trust of client